The witches eaudiobook Salem, 1692. - Schiff, Stacy (2015)
The Pulitzer Prize-winning author of Cleopatra , the #1 national bestseller, unpacks the mystery of the Salem Witch Trials. It began in 1692, over an exceptionally raw Massachusetts winter, when a minister's daughter began to scream and convulse. It ended less than a year later, but not before 19 men and women had been hanged and an elderly man crushed to death. The panic spread quickly, involving the most educated men and prominent politicians in the colony. Neighbors accused neighbors, parents and children each other. Aside from suffrage, the Salem Witch Trials represent the only moment when women played the central role in American history. In curious ways, the trials would shape the future republic. As psychologically thrilling as it is historically seminal, The Witches is Stacy Schiff's account of this fantastical story — the first great American mystery unveiled fully for the first time by one of our most acclaimed historians.